PEMBERDAYAAN MASYARAKAT MELALUI TANAMAN OBAT KELUARGA (TOGA) DAN PEMBUATAN APOTEK HIDUP DI DESA MAKMUR, KABUPATEN ACEH TENGAH, ACEH - Wahyu Firmana Isnijar; Nanda Fajar Putra; Muhammad Naufal; Zidni Ilman Navia (Fakultas Teknik, Universitas Samudra, 2023)
The aim of the research is that the people of Makmur Village use herbal plants to make more natural medicines. The dedication method used is by conducting case studies and participatory. The stages of the activity began with socializing in advance to the Makmur Village community regarding the types of herbaceous plants that could be used as toga cultivation and a demonstration of medicinal plant processing followed by the stage of making a living pharmacy. The plants cultivated in the production of live apothecary in Makmur Village are Jahe (Zingiber officinale), Lengkuas (Alpinia Pyramidata), Kencur (Kaemferia galangal), Serai (Andropogon natrus), temulawak (Curcuma Xanthorrhiza), and sirih (Piper betle). The community also knows the tools and materials used, as well as the steps in cultivating or planting living medicinal plants in their yards. So that people are more enthusiastic and interested in cultivating medicinal plants in their yards. The program to create a living pharmacy is very beneficial for the people of Indonesia, especially for Makmur Village. 6 types of herbaceous plants that have been planted are the initial capital for the development of a living pharmacy in Makmur Village. Cultivating family medicinal plants (living pharmacy) means the same as preserving the wisdom that is owned by Indonesia. The Makmur Village community will certainly have more knowledge about the use of herbal plants which will certainly encourage people to live healthily and make more use of natural medicines.